MENINGKATKAN HASIL BELAJAR SISWA KELAS X1 SMU MUHAMMADIAH BATUDAA PADA MATERI STRUKTUR ATOM MELALUI STRATEGI QUESTION STUDENT HAVE - Idrus, Selvian; Isa, Ishak; Ischak, Netty Ino (Jurnal Entropi, 2009)
This research involved X1 Grade students of SMA Muhammadiyah Batudaa with total number of students were 21 students. It consist of 9 male students and 12 female students of 2008/2009 academic years. Technique in collecting the data was observation. This research was a classroom action research and it was done during one semester as two cycles. The observation result of teacher activity in first cycle got excellent criteria as 72, 72 and good criteria as 27,27. While in second cycle, it was improved as 36 % reached excellent criteria and 64 % reached good criteria. Besides that, observation result of students in first cycle is students who got an excellent criteria was 57,13 % and good criteria was 42,85% while in second cycle it was improved, that is students who got an excellent criteria was 29% and good criteria was 71%. Students achievement in first cycle were 13 students or 61,905 got score more, than 6,9 and 8 students or 38,09% got score less than 6,9. while the students achievement in second cycle was improved. It was 18 students or 85,71% got score more than 6,9 and 3 student got score less than 6,9 with classical absorption was 71,42%.Based on that result above, the applications of question student have strategy in atom structure lesson can improve student achievement. There fore, the hypothesis in this research can be accepted.